Species composition and population dynamics of phlebotomine sand flies in a Leishmania infected area of Chiang Mai, Thailand - S. Sor-Suwan (2018)
© 2017, Malaysian Society for Parasitology. All rights reserved. Phlebotomine sand flies are established vectors of leishmaniasis in humans. In Thailand, Leishmania martiniquensis and “Leishmania siamensis” have been described as causative agents of leishmaniasis. In this study, a survey of sand flies in the Leishmania infected area of Hang Dong district, Chiang Mai, Thailand was performed using CDC light traps for eight consecutive months, from January to August 2016. A total of 661 sand flies were collected, and of 280 female sand flies, four species of the genus Sergentomyia including Sergentomyia gemmea, S. barraudi, S. indica, and S. hivernus and one species of the genus Phlebotomus, Phlebotomus stantoni, were identified. S. gemmea and S. hivernus were found in Chiang Mai for the first time. The density of captured female sand flies was high in warm and humid periods from June to August, with temperatures of around 26°C and relative humidity about 74%. In addition, S. gemmea was the most predominant species in the area. Further studies as to whether or not these sand fly species could be a vector of Leishmaniasis in Thailand are required.